Effectiveness of a peer-assisted learning model in teaching physical examination in Otorhinolaryngology to clerks and postgraduate interns - Alcantara-Capuz, Maria Karen MD; Atienza, Melflor A. (2018)
Background: To comply with an Outcome Based Educational framework, this study was conducted to determine the effectiveness of incorporating a formal, planned Peer Assisted Learning (PAL) model of instruction in helping achieve the program outcomes of clinical competence, communicating effectively, continuing personal and professional development and professional and ethical practice in the OBE curriculum for Clerks and Postgraduate Interns (PGI) rotating in the Department of Otorhinolaryngology-HeOtorhinolaryngology-Head and Neck Surgery (ORL-HNS). Methods: The study was divided into 2 parts. Part 1 was a one-group pre-test and post-test design that involved teaching training of 16 PGI under a Microteaching Supervisor to be Peer Tutors in Otorhinolaryngology Physical Examination (ORL PE) to Clerks. Video recorded Pre-training Baseline and Post-training Actual skills demonstrations of the PGI were rated by the Microteaching Supervisor and scores were compared using Wilcoxon Signed Ranks test with p value at 5% level of significance. Part 2 of the study was a randomized controlled single-blind trial of Peer-Led vs. Expert Faculty-Led ORL PE training of 55 Clerks. The trained PGI and Expert Faculty exclusively taught the randomly assigned Clerks the skills in ORL PE. Tutees thereafter performed a post training video-recorded skills demonstration which was rated by a Faculty Rater for Tutees who was blinded as to who among the Clerks underwent the PAL-Led or Expert Faculty-Led training. Scores of the tutees in the 2 models of instruction were compared using the Mann-Whitney U-test at 5% level of significance. Participants in the Peer-Led arm were asked to accomplish a self- administered Likert-type questionnaire regarding their attitude toward the PAL experience. The responses were presented in frequency tabulations. Results: For Part 1 of the study, statistical analysis showed a significant improvement between the Pre-and Post-training scores of the 16 PGI in the microskills of explaining, questioning, demonstrating and giving feedback as well as in overall ORL PE skills. For Part 2 of the study, of the 55 Clerks randomly assigned to each of the study arm, 33 underwent PAL-Led and 22 Expert Faculty-Led instruction. Comparison of scores of the Clerks under the 2 models of instruction showed no significant difference between the performance outcomes of the 2 groups. Seventy nine per cent and 64% of Clerks that underwent PAL-Led and Expert Faculty-Led tutorial respectively achieved MPL. There was a strongly positive attitude towards the PAL experience among the participants in the PAL-Led arm of the study. Conclusion: Teaching Training for PGI under a Microteaching Supervisor improved their knowledge, skills and attitude in teaching ORL PE skills to Clerks. There was no significant difference in the performance outcomes between Clerks that underwent PAL-Led and Expert Faculty-Led model of instruction. Survey results on the attitude of the participants towards their PAL experience showed a high level of acceptance and satisfaction in the ORL-HNS clinical setting. There is merit in incorporating the PAL-Led model of instruction in the curriculum for Clerks and PGI in the clinical setting of ORL-HNS as an alternative to the traditional Faculty-Led model of instruction.
Also available in pdf
Thesis (Master of Health Professions Education)--University of the Philippines Manila
Panel Members: Melflor A. Atienza MD MHPEd, Chair/Adviser; Jesus N. Sarol, Jr. PhD, Reader/Critic; Erlyn A. Sana PhD, Member; Remedios Dee-Chan MD MHPEd, Member; Josephine L. Lumitao MD MHPEd, Member.
Keywords: Peer-assisted learning; Physical examination